Peran wisata religi makam Gus Dur dalam membangun kehidupan sosial ekonomi masyarakat di sekitar pondok pesantren Tebuireng Jombang - Sela Kholidiani (Jurnal Teori dan Praksis Pembelajaran IPS, 2017)
This article aims to describe the role of religious tourism in the grave of Gus Dur in building the socio-economic life of the community around Pondok Pesantren Tebuireng Jombang and analyzing the socio-economic life. To achieve that goal, a qualitative descriptive approach is used. Data collection techniques used were observation, interview, and documentary study. Data were analyzed by reducing data, presenting data and drawing conclusions. The result of the research shows that religious tourism of Gus Dur grave is very important in building the socio-economic life of the community around Pondok Pesantren Tebuireng Jombang, especially since Gus Dur is buried in the cottage area because of the many pilgrims coming from various regions so that the surrounding community can take advantage of the opportunity to establish various kinds Kinds of business based on Islamic principles. Economic life around the Pondok Pesantren Tebuireng Jombang increased, it can be seen the increasing number of people around who opened a variety of goods and services business and their socio-economic life was also awakened by the social interaction between traders with traders and traders with buyers.Keywords: Religious Toirism, Social, Economic http://dx.doi.org/10.17977/um022v2i12017p041